Contradiction Of Using Hujjah With Daif Hadith In Fadail A'mal: Analysis of the Book of Al-Targib wa al-Tarhib - Anisah, Rafiqatul; Afabih, Abdillah (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
Scholars of hadith have mentioned that da'if (weak) hadiths can be used for Fadail Al-A'mal (virtuous actions), but it is uncertain which type of da'if hadith can be used as evidence. Although previous researchers have conducted numerous studies on this topic, this paper aims to discuss the validity of using da'if hadiths as evidence for Fadail al-a'mal by examining the types, conditions, and replacement hadiths of da'if narrations. The conclusions presented in this paper are based on the opinions of hadith scholars, taking into account both the advantages and disadvantages. The researcher employs an analytical study method, focusing on the da'if hadiths compiled in the book